EFFECTIVENESS MONTASE AS TUBERCULOSIS AWARENESS PROGRAM AND ASSOCIATED CHANGES IN KNOWLEDGE LEVELS OF THE FAMILIES - Linda Widyarani; Cecilya Kustanti (Department of Nursing, Faculty of Health Sciencce, Universitas Brawijaya, 2020)
The success of TB control is strongly influenced by the role and support of the family.Families who do not care, do not support treatment programs, tend to be ignorant, donot make efforts to prevent transmission in the care of family members with TB, and givenegative stigma against TB disease has a negative impact on the success of TB control.One of the efforts to build and increase the role of the family in TB control is to provideeducation on prevention of transmission in the care of family members with TB using theMontage method. This study aims to determine the effectiveness of the montage learningmethod in increasing knowledge about control and prevention of transmission in thecare of family members with TB. This study used a quasi-experimental method withone group pre-post test design. We obtain 31 respondents with a purposive samplingtechnique. The intervention used is application of 3M art, namely folding, cutting andpasting pictures on paper that form pictorial stories. In this study, the average pretestvalue was 48.39 Â± 5.536 and the posttest value was 73.23 Â± 11.729, with a p-value of0.000, which means that there was a significant difference between the knowledgebefore and after the intervention. Therefore, the strategy of providing education withthe montage learning method needs to be integrated into the promotional program.